Q. 175.0( 1 Vote )

# Evaluate the foll

Formula used:

where,

Let,

Here, f(x) = cos x

Now, by putting x = a in f(x) we get,

f(a) = cos a

f(a + h)

= cos (a + h)

Similarly, f(a + 2h)

= cos (a + 2h)

We know,

Therefore,

{ nh = b – a}

{ 2 cos A sin B = sin(A + B) – sin(A – B)}

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

<span lang="EN-USRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2

Evaluate the follRD Sharma - Volume 2